VISUM ET REPERTUM SEBAGAI ALAT BUKTI KONKRIT DALAM MENCARI KEBENARAN MATERIIL PADA PEMBUKTIAN TINDAK PIDANA - REVI ASTUTI (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Evidence is the most important thing in the process of proof in a criminal court. Some cases, such as cases of assault, rape / immoral to murder Visum et Repertum have absolute power in proof, because Visum et Repertum is examined not only on the outside of the victim but on the inside of the victim. Therefore, the results of the Visum et Repertum are used as authentic evidence in seeking actual material truths. The research method, this research uses normative juridical, with a conceptual approach, namely analyzing legal materials from a knowledge and practical point of view, where the result is that the strength of the results of Visum et Repertum can be used as absolute evidence in proving in the legal court process in order to uphold the truth and the fairest.